Association of BoLA-DRB3 and TLR4 alleles with subclinical mastitis in cattle from Colombia (2014)
ABSTRACT: molecular markers for genetic resistance can be used to control mastitis in dairy cattle. The Major Histocompatibility Complex and the Toll-like receptor 4 (TLR4) are two promising genes that warrant investigation. Objective: to identify associations between genotypes of BoLA-DRB3 locus and T4CRBR2 fragment and subclinical mastitis (SM). Methods: 996 lactating cows from 32 herds comprising Holstein (80%), Holstein x Jersey cross (12.5%), and other crosses (7.5%) were evaluated monthly during two years, diagnosed for SM and genotyped for the second exon of BoLA DRB3 and the TLR4 coreceptor-binding region 2 (T4CRBR2) using a Polymerase chain reaction-restriction fragment length polymorphism technique (PCR-RFLP). The association between candidate alleles and subclinical mastitis was measured by logistic regression. Results: the most frequently observed alleles for BoLA-DRB3 were DRB3.2 *8, *22, *24, *16, *10, *23, *gba, *11, *2, *mbb, *jba, *3, and *15, accounting for 58.9% of the population. Frequencies for T4CRBR2 alleles A and B were 0.352 and 0.647, respectively. Based on 57,408 observations during the period, the mean SM prevalence was 16.2% (95% CI 13.0 and 19.4) per udder quarter and 37.6% (95% CI 32.1 and 43.2) per cow. The predominant microorganisms isolated from SM quarters were Streptococcus agalactiae and Coagulase-Negative Staphylococci (CNS). Allele DRB3.2 *23 was associated with SM occurrence and CNS infection. No alleles were associated with Streptococcus agalactiae infection. Allele *mbb was associated with occurrence of CNS infection and alleles *jba and *15 were associated with resistance to CNS infection. No significant relationship between T4CRBR2 and SM was observed. Conclusion: DRB3.2 gen may play an important role in the occurrence of SM and certain alleles may confer resistance to specific pathogens.